Molecular aspects of cell-penetrating peptides: key amino acids, membrane partners, and non-covalent interactions - Walrant, Astrid; Tazi, Farah; Khemaissa, Sonia; Sagan, Sandrine (Comptes Rendus. Chimie)
Since the early 1990s, there has been considerable interest in cell-penetrating peptides (CPPs) capable of transporting various types of molecules in cells. These CPPs are endowed with the ability to cross the cell membrane by endocytosis and by other, as yet poorly understood, translocation pathways. Translocation involves interactions of the peptide with plasma membrane components before it can contact, disrupt, and/or reorganize the lipid bilayer. The plasma membrane is complex in terms of molecular composition and structure. It separates the external environment from the cell interior and is composed of thousands of different lipids, proteins, and sulfated carbohydrates, all arranged in a complex and dynamic manner and at various length scales. Floating above the lipid bilayer, negatively charged proteoglycans and other polysaccharides form a viscous, anionic matrix layer surrounding animal cells, which CPPs have to go through to reach the lipid bilayer. Even though the thickness and structure of this glycocalyx are extremely variable in different cell types, CPPs can cross ubiquitously cell membranes. On the peptide side, CPPs are mostly short (less than 30 amino acids), positively charged sequences. Some have also primary or secondary amphipathic properties. Understanding CPP translocation pathways requires interdisciplinary approaches from physical chemistry to cell biology for identifying key amino acids in the peptide sequence and membrane components, and the interactions between the two involved in the different steps of the process. In the following synthetic review, we focus on these aspects.